Balance and coordination after viewing stereoscopic 3D television. Issue 7 (July 2015) - Read, Jenny C. A.; Simonotto, Jennifer; Bohr, Iwo; Godfrey, Alan; Galna, Brook; Rochester, Lynn; Smulders, Tom V.
Abstract : Manufacturers and the media have raised the possibility that viewing stereoscopic 3D television (S3D TV) may cause temporary disruption to balance and visuomotor coordination. We looked for evidence of such effects in a laboratory-based study. Four hundred and thirty-three people aged 4–82 years old carried out tests of balance and coordination before and after viewing an 80 min movie in either conventional 2D or stereoscopic 3D, while wearing two triaxial accelerometers. Accelerometry produced little evidence of any change in body motion associated with S3D TV. We found no evidence that viewing the movie in S3D causes a detectable impairment in balance or in visuomotor coordination.